FRI0649-HPR HYDROXYCHLOROQUINE PRESCRIBING AND OPHTHALMOLOGY SCREENING WITHIN RHEUMATOLOGY DEPARTMENTS IN THE NORTH-WEST OF THE UNITED KINGDOM: A PROSPECTIVE REGIONAL AUDIT. (2nd June 2020) - Juman, S.; David, T.; Gray, L.; Hamad, R.; Horton, S.; Ibrahim, M.; Khan, B.; Khazaleh, Y.; Porter, M.; Sheikh, A.; Ho, P.; Wig, S.; et al.
Abstract : Background: Hydroxychloroquine (HCQ) is widely used in the management of rheumatoid arthritis and connective tissue disease. The prevalence of retinopathy in patients taking long-term HCQ is approximately 7.5%, increasing to 20-50% after 20 years of therapy. Hydroxychloroquine prescribed at ≤5 mg/kg poses a toxicity risk of <1% up to five years and <2% up to ten years, but increases sharply to almost 20% after 20 years. Risk factors for retinopathy include doses >5mg/kg/day, concomitant tamoxifen or chloroquine use and renal impairment. The UK Royal College of Ophthalmologists (RCOphth) 2018 guidelines for HCQ screening recommend optimal treatment dosage and timing for both baseline and follow-up ophthalmology review for patients on HCQ, with the aim of preventing iatrogenic visual loss. This is similar to recommendations made by the American Academy of Ophthalmology (2016). Objectives: To determine adherence to the RCOphth guidelines for HCQ screening within the Rheumatology departments in the North-West of the UK. Methods: Data for patients established on HCQ and those initiated on HCQ therapy were collected over a 7 week period from 9 Rheumatology departments. Results: 473 patients were included of which 56 (12%) were new starters and 417 (88%) were already established on HCQ. 79% of the patients were female, with median ages of 60.5 and 57 years for new and established patients respectively. The median (IQR) weight for new starters was 71 (27.9) kg and for established patients, 74 (24.7) kg. 20% of new starters exceeded 5mg/kg daily HCQ dose. 16% were identified as high risk (9% had previously taken chloroquine, 5% had an eGFR <60ml/min/m 2 and 2% had retinal co-pathology). Of the high-risk group, 44% were taking <5mg/kg. In total, 36% of new starters were referred for a formal baseline Ophthalmology review. In the established patients, 74% were taking ≤5mg/kg/day HCQ dose and 16% were categorized as high risk (10% had an eGFR less than 60ml/min/m 2, 3% had previous chloroquine or tamoxifen use and 2% had retinal co-pathology). In the high-risk group, 75% were not referred for spectral domain optical coherence tomography (SD-OCT). 41% of patients established on HCQ for <5 years, and 33% of patients on HCQ for >5 years were not referred for SD-OCT. Reasons for not referring included; awaiting 5 year review, previous screening already performed and optician review advised. Since the introduction of the RCOphth guidelines, 29% patients already established on HCQ had an alteration in the dosage of HCQ in accordance with the guidelines. In the high-risk group, 16% were not on the recommended HCQ dose. Conclusion: This audit demonstrates inconsistencies in adherence to the RCOphth guidelines for HCQ prescribing and ophthalmology screening within Rheumatology departments in the North-West of the UK for both new starters and established patients. Plans to improve this include wider dissemination of the guidelines to Rheumatology departments and strict service level agreements with ophthalmology teams to help optimize HCQ prescribing and screening for retinopathy. Acknowledgments: Drs. S Jones, E MacPhie, A Madan, L Coates & Prof L Teh. Co-1st author, T David. Disclosure of Interests: None declared